Capsule endoscopy in clinical practice: four years of experience from a single center - Freitas,Gustavo Pignaton de (2011)
Capsule endoscopy is a diagnostic method of increasing use nowadays, with various applications such as, evaluation of obscure gastrointestinal bleeding, chronic diarrhea and anemia. The experience of 4 years is reported in a retrospective review of 109 medical records to determine the main indications and the most common diagnostic findings and the percentage of positive studies. The main indications were obscure bleeding in 65%, chronic anemia in 8%. Vascular lesions in 33%, being that, hematocistic spot was found in 53% of studies. The location of active bleeding was possible in five patients (4.5%). Capsule endoscopy shows a high diagnostic yield in obscure bleeding.